Komparasi Dampak Sukuk dan Obligasi Negara terhadap Pembangunan Berkelanjutan di Indonesia - Sofia Lutfiyati; Muhammad Amin; Lise Purnamasari (Global Sustainability Research Institute, 2026)
Introduction: Sustainable development requires substantial financing, particularly to support SDG 8 (economic growth) and SDG 9 (infrastructure), the two goals most relevant to sukuk and government bonds as state financing instruments. This study compares the impact of sukuk and government bonds Indonesia's two main capital market financing instruments, which differ in structure, mechanism, and investor baseon sustainable development during 2020–2024, a period reflecting post-pandemic financing dynamics with complete official data availability.Methods: Using five years of secondary time-series data from DJPPR, the Ministry of Finance, and BPS, this study applies Ordinary Least Squares (OLS) regression to assess the effect of sukuk and bond issuance and outstanding values on GDP (economic growth indicator) and the National Road Network (infrastructure indicator).Results: Outstanding sukuk significantly and positively affect GDP, while sukuk issuance, bond issuance, and outstanding bonds show no significant effect on GDP or the National Road Network. Simultaneously, sukuk and bonds significantly influence GDP but not the National Road Index.Conclusion and suggestion: Sukuk outperform government bonds as a strategic instrument for financing Indonesia's sustainable development, especially in driving economic growth, though both instruments' limited effect on infrastructure suggests a need for better allocation of financing proceeds. Future research should extend the study period, add macroeconomic control variables, and use broader infrastructure indicators.